Non-parametric Bayesian models of response function in dynamic image sequences - Tichý, Ondřej; Šmídl, Václav (Computer vision and image understanding, 2016)
•Bayesian blind source separation and deconvolution problem is introduced.•Source dynamics is a result of convolution of unknown input and response functions.•We propose and study five non-parametric prior models of the response functions.•We analyze performance and behavior of the proposed models on synthetic data.•Dynamic scintigraphy experiments demonstrate potential of the method in practice. Estimation of response functions is an important task in dynamic medical imaging. This task arises for example in dynamic renal scintigraphy, where impulse response or retention functions are estimated, or in functional magnetic resonance imaging where hemodynamic response functions are required. These functions can not be observed directly and their estimation is complicated because the recorded images are subject to superposition of underlying signals. Therefore, the response functions are estimated via blind source separation and deconvolution. Performance of this algorithm heavily depends on the used models of the response functions. Response functions in real image sequences are rather complicated and finding a suitable parametric form is problematic. In this paper, we study estimation of the response functions using non-parametric Bayesian priors. These priors were designed to favor desirable properties of the functions, such as sparsity or smoothness. These assumptions are used within hierarchical priors of the blind source separation and deconvolution algorithm. Comparison of the resulting algorithms with these priors is performed on synthetic datasets as well as on real datasets from dynamic renal scintigraphy. It is shown that flexible non-parametric priors improve estimation of response functions in both cases. MATLAB implementation of the resulting algorithms is freely available for download.